The Effectiveness of Brief Information and Self-Efficacy-Based Interventions in Influencing Snack Choices in Homeless Individuals - Chris Emmerson; Bev John; Susan Faulkner; Deborah Lancastle; Gareth Roderique-Davies (Frontiers Media S.A., 2017)
BackgroundHomeless adults frequently experience poor nutrition. Research suggests raising self-efficacy and nutritional knowledge can increase healthy eating but that the choice of specific behavioral change techniques (BCTs) is also critical. This study investigated how BCTs, operationalized to increase nutrition knowledge and self-efficacy, might influence the choice of homeless adults when presented with a "healthy" and an "unhealthy" snack.MethodsA total of 125 homeless adults were randomly allocated to watch 1 of 4 brief films: "control," "[nutrition] information only," "self-efficacy" (aimed at increasing self-efficacy and general healthy eating knowledge), and "enhanced self-efficacy" (as "self-efficacy," but the presenter identified themselves as a homeless adult). Post-film, participants were invited to choose between a healthy and an unhealthy snack. Data were analyzed using ANOVA and chi square.ResultsParticipants in the "enhanced self-efficacy" condition were significantly more likely to choose the healthy option compared to those in the control condition; for the "self-efficacy" condition, the difference was marginally significant. Perceived knowledge and self-efficacy were significantly associated and those with high self-efficacy were significantly more likely to choose a healthy snack regardless of condition.ConclusionHomeless adults are more likely to make healthy snack choices if their nutritional self-efficacy is increased through encouragement by a peer.